PKM Pendampingan dan Perbaikan Proses Produksi Sabun di UKM Berdikari Soap serta Diversifikasi Produk dan Strategi Pemasaran - Alti, Rahmi; Putri, Intan Cynara Valentina; Agustianti, Rifka (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This PKM activity has promising prospects in developing home industry entrepreneurship. After this activity is carried out, partners receive education and guidance on how to make good soap with the help of soap calc computing software and get procurement for the tools needed to make soap. Partners get a perspective on product diversification, so that they have more variants of soap that are worth selling with attractive and eco-friendly packaging. Partners have also started using the internet, especially marketplaces and social media, to expand market reach.